PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Rosiana Wisuda Putri; Puji Astuti (Jurnal Fokus Manajemen Bisnis, 2022)
This study aims to determine the effect of training and work motivation on employee performance at Perum Damri Yogyakarta Branch Office. This type of research uses quantitative methods using the Statistical Package for the Social Sciences (SPSS) program. Methods of obtaining data using questionnaires and interviews. The sample used was 48 employees of the Perum Damri Yogyakarta Branch Office. The tests used are validity tests, reliability tests, multiple linear regression analysis, and statistical tests. Based on the results of statistical tests, training and work motivation positively influence the performance of employees of the Perum Damri Yogyakarta Branch Office.